“APPROACH IS MERELY A LENS…”: A STYLISTIC ANALYSIS OF LITERATURE CLASSROOM DISCOURSE - Afrianto Afrianto; Mohamad Adriansyah (Universitas Teknokrat Indonesia, 2023)
This study looks at the lecturer's linguistic style when delivering material on literary criticism. In this instance, the emphasis is on the stylistic analysis to expose the usage of figurative language and its role in the dialogue between the lecturer and the students. Therefore, the purpose of this study is to examine the figurative language used by a lecturer in a literary class. This study employs the qualitative technique and selects a participant based on the requirements of having a master's degree, having 10 years of teaching experience, and being recommended in order to have an in-depth talk. The data, which are expressed as words, phrases, or sentences, are acquired from audio-video recordings of spoken speech. The recording was made during a lecture in a classroom to obtain an actual situation of the recordings. Furthermore, this study discovered twelve types of figurative language used by the lecturer: metaphor, simile, personification, apostrophe, metonymy, synecdoche, symbol, allegory, paradox, irony, hyperbole, and litotes. Also, each figurative language has a function to convey a particular meaning; comparison, association, and contrast. In addition, the results demonstrate that through the use of figurative language, the lecturer has more alternative ways to expand on the learning subject in the classroom and to enhance students' awareness of stylistics in the form of figurative language.